The influence of migrations on the ethnic/national and religious identities: The case of the united Methodist Church in Banat - Blagojević Gordana (Glasnik Etnografskog Instituta SANU, 2014)
This research focuses on the correlation between migrations and ethnic and religious identities on the example of the United Methodist Church (UMC)2 in Banat. This paper observes a complex network of social, political and cultural factors which induced the changing of the number of members of the UMC local congregations, and their ethnic structure. Ever since the founding of the first UMC congregations on the territory of Serbia (mostly in Vojvodina) at the beginning of the 20th century until the end of World War II, the greatest number of their members were German. After they had immigrated, there was a sharp membership decline and many UMC congregations were extinguished. Today there are four UMC congregations in Banat, the largest one being the Macedonian Roma congregation in Jabuka, which is called the ’’Roma church’’ by the local people. Protestant congregations in Serbia are minority denominations and the UMC in Banat does not have many members. In the UMC in Jabuka the pastor is a woman, which is also very rare. [Projekat Ministarstva nauke Republike Srbije, br. 177027: Multiethnicity, Multiculturalism, migrations: Contemporary process]